The Validity of E-Signature in Authentic Deeds as Digital Transformation of Notaries - Mazwar, Mazwar; Handoko, Widhi; Sri Darmadi, Nanang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to analyze: 1) The validity of e-signature in authentic deeds according to the prevailing laws and regulations in Indonesia. 2) Challenges and solutions in the application of e-signature in authentic deeds by notaries. This type of research is included in the scope of normative legal research. The approach method in this research is legislation (statue approach). The type of data in this research is secondary data sourced from primary, secondary and tertiary legal materials. The data collection method uses library techniques (study document). The analysis in this research is qualitative analysis. The results of the research concluded: 1) The validity of e-signature in authentic deeds according to the prevailing laws and regulations in Indonesia is still at the conceptual stage and does not yet fully have strong normative legitimacy. In positive law, Law Number 1 of 2024 concerning the Second Amendment to the ITE Law has provided a basis for recognizing electronic signatures as valid evidence, as regulated in Article 11 paragraph (1) and Article 5 paragraph (1). However, this recognition has not been harmoniously accommodated in Law Number 2 of 2014 concerning the Position of Notary, which still requires physical presence and manual signature as stated in Article 16 paragraph (1) letter m. The lack of synchronization between the two laws creates legal uncertainty regarding the authenticity of deeds made electronically. 2) The implementation of e-signatures in authentic deeds by notaries still faces various challenges that are normative, technical, and sociological. The disharmony between the ITE Law, PP No. 71 of 2019, and the Notary Position Law is the main obstacle that causes the lack of legal certainty regarding the validity of electronic deeds. On the other hand, limited digital infrastructure and low technological literacy among notaries and the public also slow down the process of notarial digitalization. Nevertheless, solution efforts in the form of regulatory harmonization, strengthening cybersecurity systems through Electronic Certification Providers (PSrE), and increasing notary digital competence are strategic steps that must be implemented immediately to ensure that electronic deeds have the same legal force as conventional authentic deeds. Thus, the success of the digital transformation of notaries can only be achieved if law, technology, and the ethics of the notary profession work in harmony to ensure legal certainty, justice, and legal protection for the parties.